PENGARUH VARIASI PARAMETER PEMOTONGAN TERHADAP PANAS YANG TERBAWA OLEH GERAM PADA MESIN FREIS HERCUS CF 7264 - Padangi, Dalton; Poeng, Rudy; Ulaan, Tertius (Jurnal Poros Teknik Mesin UNSRAT, 2024)
The purpose of this research is to get the relationship, predict the relationship and analyze the effect of variations in cutting parameters on the heat of heat that is carried by the gristle on the HERCUS CF 7264 freis machine. This research is an experimental research, namely by conducting tests on the freis machine in the Unsrat Mechanical Engineering Laboratory by varying the cutting parameters in the form of freis machine rotation as an independent variable to obtain the heat that is carried by the slurry as the dependent variable. The results of the analysis of this study are from 12 tests with variations in cutting parameters in the form of freis machine rotation to the heat carried by the graver. It can be seen that the actual relationship is that with the increase in the rotation of the freis machine, the heat carried by the grind increases. The results of simple linear regression analysis obtained the regression line equation y ̂ = 47.75 + 0.095x. This shows the effect of variations in cutting parameters in the form of milling machine rotation on the heat carried by the slurry on the HERCUS 7264 milling machine which predicts that every increase in rotation of 1 rpm, the heat with the down milling feeding direction will increase by 0.095 J/min. Keywords: Cutting Parameters, Carried Heat by Grind, Freis Machine HERCUS CF 7264